Memahami T1 dan T2 melalui Pulsed NMR: Sebuah Studi Literatur tentang Relaksasi Spin dalam Sistem Magnetik - Maria Tefa; Hartoyo Yudhawardana; Aurelia Astria L. Jewaru; Markus Simeon K. Maubuthy (Pusat riset dan Inovasi Nasional, 2025)
The Pulsed Nuclear Magnetic Resonance (PNMR) technique is a widely used spectroscopic approach for observing the relaxation phenomena of atomic nuclei in a magnetic field. In this technique, the spin-lattice (T1) and spin–spin (T2) relaxation times are key parameters, as they reflect the microscopic dynamics and structure of a material system. This article presents the results of a systematic literature review of fourteen primary references that discuss the fundamental concepts of NMR, PNMR techniques, the measurement of T1 and T2, and PNMR applications. Although NMR research has seen extensive development internationally, scientific literature in the Indonesian language that specifically addresses this topic remains scarce. Therefore, this paper is intended to serve as an initial systematic resource to introduce the basic principles and potential applications of PNMR in physics and materials science.